A detailed proteomic profiling of plasma membrane from zebrafish brain. Issue 12 (12th August 2016) - Smidak, Roman; Aradska, Jana; Kirchberger, Stefanie; Distel, Martin; Sialana, Fernando J.; Wackerlig, Judith; Mechtcheriakova, Diana; Lubec, Gert
Abstract : Zebrafish ( Danio rerio ) is a well‐established model organism in developmental biology and disease modeling. In recent years, an increasing amount of studies used zebrafish to analyze the genetic changes underlying various neurological disorders. The brain plasma membrane proteome represents the major subsets of signaling proteins and promising drug targets, but is often understudied due to traditional experimental difficulties including problems with solubility, detergent removal, or low abundance. Here, we report a comprehensive dataset of the proteins identified in the enriched plasma membrane of the zebrafish brain by applying sequential trypsin/chymotrypsin digestion with multidimensional LC‐MS/MS. A total number of 97 017 peptide groups corresponding to 9201 proteins were identified. These were annotated in various molecular functions or neurological disorders. The dataset of the current study provides a useful data source for further utilizing zebrafish in basic and clinical neuroscience.